2020
DOI: 10.29333/ejeph/8288
|View full text |Cite
|
Sign up to set email alerts
|

Industrial Emissions and Asthma Prevalence

Abstract: The pathogenesis of asthma is multifactorial and not completely understood; however, it is considered a chronic inflammatory disease that affects the airways and has a clinical development of wheezing, shortness of breath, chest tightness, and cough. The prevalence of asthma has increased drastically during the past few decades. Urban air pollution from industrial emissions has been implicated as one of the major factors responsible for this increase. The objective of this paper was to analyze the impact of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 48 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…Few studies have noted that the CO 2 levels of 600-800 ppm indicate inadequate ventilation rates [98,99]. Exposure to higher CO 2 concentrations is associated with asthma [100,101], reduced work performance, and increased harmful health symptoms [102]. Shendell et al reported the association of student absences with CO 2 concentration where the value of 1000 ppm CO 2 is associated with a 10%-20% increase in student absence [46], thus indicating CO 2 concentrations to be an important parameter in the health risk assessment of school students [27].…”
Section: Carbon Dioxide Concentrations and School Ventilationmentioning
confidence: 99%
“…Few studies have noted that the CO 2 levels of 600-800 ppm indicate inadequate ventilation rates [98,99]. Exposure to higher CO 2 concentrations is associated with asthma [100,101], reduced work performance, and increased harmful health symptoms [102]. Shendell et al reported the association of student absences with CO 2 concentration where the value of 1000 ppm CO 2 is associated with a 10%-20% increase in student absence [46], thus indicating CO 2 concentrations to be an important parameter in the health risk assessment of school students [27].…”
Section: Carbon Dioxide Concentrations and School Ventilationmentioning
confidence: 99%
“…SO 2 and NO emissions are important contributors to air pollution. These emissions have negative effects on human health, particularly on the respiratory system. Furthermore, SO 2 and NO are responsible for acid rain and ozone depletion . Increased environmental consciousness and worldwide sustainable development have led to increasingly strict industrial emission requirements.…”
Section: Introductionmentioning
confidence: 99%